Cross-Talk between P2X and NMDA Receptors - Larry Rodriguez (International Journal of Molecular Sciences, 2020)
Purinergic P2X receptors (P2X) are ATP-gated ion channels widely expressed in the CNS. While the direct contribution of P2X to synaptic transmission is uncertain, P2X reportedly affect N-methyl-D-aspartate receptor (NMDAR) activity, which has given rise to competing theories on the role of P2X in the modulation of synapses. However, P2X have also been shown to participate in receptor cross-talk: an interaction where one receptor (e.g., P2X2) directly influences the activity of another (e.g., nicotinic, 5-HT3 or GABA receptors). In this study, we tested for interactions between P2X2 or P2X4 and NMDARs. Using two-electrode voltage-clamp electrophysiology experiments in Xenopus laevis oocytes, we demonstrate that both P2X2 and P2X4 interact with NMDARs in an inhibited manner. When investigating the molecular domains responsible for this phenomenon, we found that the P2X2 c-terminus (CT) could interfere with both P2X2 and P2X4 interactions with NMDARs. We also report that 11 distal CT residues on the P2X4 facilitate the P2X4–NMDAR interaction, and that a peptide consisting of these P2X4 CT residues (11C) can disrupt the interaction between NMDARs and P2X2 or P2X4. Collectively, these results provide new evidence for the modulatory nature of P2X2 and P2X4, suggesting they might play a more nuanced role in the CNS.